A proposed strut efficiency factor for strut-and-tie design of steel fibre-reinforced concrete. (2022) - Ng, L.T.; Tang, A.C.S.; Looi, D.T.W.
Abstract: Strut-and-tie model (STM) is a lower-bound plastic theory to achieve force equilibrium. It uses a simplified truss analogy method to define the load transfer mechanism in the disturbed region (D-region) in concrete structures. STM was mostly applied in the design of conventional reinforced concrete (RC), and there were few discussions on the use of STM for newer concrete technology, e.g., steel fibre-reinforced concrete (SFRC). SFRC presents opportunities in reducing web reinforcements in serviceability checks and in improving the ductility of D-regions. In this paper, a strut efficiency factor for STM is proposed for the design of SFRC by collecting a database of SFRC deep beams. It was discovered that the strut efficiency factor best fits with a function of the product of the fibre factor and concrete cylinder compressive strength. Baseline deep beam numerical models were developed and calibrated with the experimental load-displacement graphs collected through literature. A parametric study with variables such as concrete cylinder compressive strengths, fibre volumes and strut angles were investigated. The proposed strut efficiency factor was found to have a peak capacity lower than the ultimate load capacity computed in the calibrated numerical models, which justified the safe use of STM as a lower-bound plastic method in SFRC.